2010
DOI: 10.3348/kjr.2010.11.4.480
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Features of Pediatric Pentastomiasis Infection: a Case Report

Abstract: We report here a case of pentastomiasis infection in a 3-year-old girl who had high fever, abdominal pain, abdominal tension and anemia. Ultrasound scanning of the abdomen revealed disseminated hyperechoic nodules in the liver and a small amount of ascites. Abdominal MRI showed marked hepatomegaly with disseminated miliary nodules of high signal intensity throughout the hepatic parenchyma on T2-weighted images; retroperitoneal lymphadenopathy and disseminated miliary nodules on the peritoneum were also noted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Human infection is as the result of ingestion of third stage larvae of L.serrata found in raw liver or lymph nodes of sheep, goats, cattle and camels. Ingestion of L. serrata nymphs can cause halzoun or marrara syndrome that is often characterized by inflammation of the upper respiratory tract, swelling of the submaxillary and cervical lymph nodes and occasionally abscess formation in the eyes or ears [31][32][33][34][35][36][37][38]9] , Sporadic incidence of halzoun in humans has also been reported in Iran [7] . The high prevalence of infection observed in ruminants is of concern owing to the zoonotic nature of the parasite and the risk of infection to humans and other animals.…”
Section: Discussionmentioning
confidence: 99%
“…Human infection is as the result of ingestion of third stage larvae of L.serrata found in raw liver or lymph nodes of sheep, goats, cattle and camels. Ingestion of L. serrata nymphs can cause halzoun or marrara syndrome that is often characterized by inflammation of the upper respiratory tract, swelling of the submaxillary and cervical lymph nodes and occasionally abscess formation in the eyes or ears [31][32][33][34][35][36][37][38]9] , Sporadic incidence of halzoun in humans has also been reported in Iran [7] . The high prevalence of infection observed in ruminants is of concern owing to the zoonotic nature of the parasite and the risk of infection to humans and other animals.…”
Section: Discussionmentioning
confidence: 99%
“…8,16 In a survey, adult parasites were recovered from two of six P. reticulatus , 16 a snake also endemic to Malaysian Borneo. It is well-known that consumption of snake meat is a common practice in some parts of Southeast Asia, [16][17][18][19] and among the aboriginal tribes in Malaysia, the Temiar, Semai, and Temuan are known habitual python eaters. 7 Risk factors for infection include consumption of undercooked contaminated snake meat as well as contact with living snakes and their secretions (i.e., tropical snake farming, pet keeping, harvesting of their skins, or tribal totemism).…”
Section: Discussionmentioning
confidence: 99%
“…Human nasopharyngeal infections may occur through consumption of raw or undercooked liver, lymph node, or other infected visceral organs, while the visceral form occurs through eating the eggs in contaminated water, vegetables, or fruits (El-Hassan et al 1991;Yagi et al 1996;Lazo et al 1999;Yao et al 2008;Tappe and Büttner 2009). Human linguatulosis is reported from various parts of the world such as Germany (Tappe et al 2006;Tappe and Buttner 2009), Italy (Pampiglione et al 2001), Michigan, USA (Gardiner et al 1984), North Carolina, USA (Baird et al 1988), Canada (Guardia et al 1991), Brazil (Machado et al 2006), Ecuador (Lazo et al 1999), China (Ma et al 2002;Yao et al 2008;Lai et al 2010), Turkey (Akyol et al 1995), Egypt (Morsy et al 1999), and Sudan (Yagi et al 1996). Yao et al (2008) showed that, compared to the nasopharyngeal form, the visceral form was more common and it accounted for 88.9% of the human pentastomiasis.…”
Section: Introductionmentioning
confidence: 99%